Open Government Model and Basic Services Management: a Systematic Review - Sánchez, MPA. Lorena Beatriz Tume; Huamán, MSc. Anthony Carmen; Talledo, MPA. Luis Rubén Castillo; Sánchez , C. E. Luis Ángel Tume (Journal of Ecohumanism, 2024)
This article presents a systematic review of the literature on the Open Government model and its impact on the management of basic services in Peru, analyzing studies published in the last five years in the following databases: Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex and the University of César Vallejo library. The benefits and challenges associated with the implementation of this model are examined, highlighting its potential to improve transparency, citizen participation and collaboration between government and civil society. Through an exhaustive analysis of various research, factors that facilitate and hinder the effectiveness of Open Government are identified, such as distrust of institutions and the lack of inclusive strategies. The findings suggest that, although Open Government can be a driver to transform public management, it is essential to strengthen institutional capacities and foster a civic culture that promotes access to information and the active participation of citizens. This study provides practical recommendations for policy makers and contributes to academic understanding of open governance in the Peruvian context.